Skills For Adapting Physical Exercises to Children's Age in The Education of a Developed Generation - Abdurahmanov Murodjon Sayitqulovich (Zien Journals, 2021)
The article discusses a healthy lifestyle, exercise, which is one of the main health measures, physical education activities and their importance in raising a harmoniously developed generation.
Keywords: Harmoniously developed generation; healthy lifestyle; health; exercise